Multi-omics analysis reveals niche and fitness differences in typical denitrification microbial aggregations. (November 2019) - Deng, Yale; Ruan, Yunjie; Ma, Bin; Timmons, Michael B.; Lu, Huifeng; Xu, Xiangyang; Zhao, Heping; Yin, Xuwang
Abstract: Suspended floc and fixed biofilm are two commonly applied strategies for heterotrophic denitrification in wastewater treatment. These two strategies use different carbon sources and reside within different ecological niches for microbial aggregation, which were hypothesized to show distinct microbial structures and metabolic fitness. We surveyed three floc reactors and three biofilm reactors for denitrification and determined if there were distinct microbial aggregations. Multiple molecular omics approaches were used to determine the microbial community composition, co-occurrence network and metabolic pathways. Proteobacteria was the dominating and most active phylum among all samples. Carbon source played an important role in shaping the microbial community composition while the distribution of functional protein was largely influenced by salinity. We found that the topological network features had different ecological patterns and that the microorganisms in the biofilm reactors had more nodes but less interactions than those in floc reactors. The large niche differences in the biofilm reactors explained the observed high microbial diversity, functional redundancy and resulting high system stability. We also observed a lower proportion of denitrifiers and higher resistance to oxygen and salinity perturbation in the biofilm reactors than the floc reactors. Our findings support our hypothesis that niche differences caused a distinct microbial structure and increased microbial ecology distribution, which has the potential to improve system efficiency and stability. Graphical abstract: Unlabelled Image Highlights: Multi-omics approaches were used to investigate the microbial aggregations for denitrification. Carbon source plays an important role in microbial community composition. More nodes with less interactions were detected in biofilm than floc samples. Niche heterogeneity was positively correlated with microbial diversity and stability.